2019
DOI: 10.1038/s41598-019-39337-5
|View full text |Cite|
|
Sign up to set email alerts
|

Statistics of thermomagnetic breakdown in Nb superconducting films

Abstract: Superconductors are well known for their ability to screen out magnetic fields. In type-II superconductors, as the magnetic field pressure is progressively increased, magnetic flux accumulates at the periphery of the sample, very much like charges accumulate in a capacitor when voltage is increased. As for capacitors, exceeding certain threshold field causes the blocked magnetic flux to abruptly penetrate into the sample. This phenomenon, triggered by a thermomagnetic instability, is somewhat analogous to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
(44 reference statements)
2
10
0
Order By: Relevance
“…First, largescale, very fast (see the video in supplemental information), dendritic avalanches similar in their appearance to lightning strikes. Similar behavior was observed long ago in various films, particularly niobium, and is wellunderstood [51,52]. The physics behind it is straightforward.…”
Section: Resultssupporting
confidence: 78%
“…First, largescale, very fast (see the video in supplemental information), dendritic avalanches similar in their appearance to lightning strikes. Similar behavior was observed long ago in various films, particularly niobium, and is wellunderstood [51,52]. The physics behind it is straightforward.…”
Section: Resultssupporting
confidence: 78%
“…With the years, researchers have first learnt to mitigate the wearout problem, and later on to master it. As of today, some degree of control of this inherently stochastic phenomenon has been achieved, permitting to create nanogaps for addressing nanoclusters or single molecules [2][3][4], locally modify the geometry or the material properties to fabricate point contacts [5][6][7], superconducting weak links [8][9][10], nanoheaters [11], plasmonic nanoantennas [12], etc. In addition, recent works also showed that the change of electrical resistance in random networks of conducting nanowires under electric bias can induce percolation in these materials, making them interesting transparent conducting materials suitable in a wide range of applications, as window electrodes, transparent heaters, antennas, etc [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the morphology of flux avalanches is strongly influenced by the temperature [1,47]. Figures 3(a)-(d) show the magnetic flux distribution in the ring exposed to an increasing applied field with μ 0 Ḣa = 100 T s −1 at four different temperatures, where panels (a)-(c) correspond to the first magnetic perforation.…”
Section: Numerical Simulations Of Superconducting Ringsmentioning
confidence: 99%